DEFENSE ATTORNEY REQUEST AS THE MEANS OF OBTAINING INFORMATION ON THE CASE - Fink Денис Александрович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2021)
The search and collection of evidence by a lawyer is a process of cognition of a criminal event and other related circumstances of the surrounding reality, taking into account the tasks of his professional activity. The purpose of this activity is information captured on objects-carriers - objects, documents, memory of a living person. The basis for exercising the powers of a lawyer to collect factual data mitigating or refuting the charges brought against the client by sending inquiries to state and other institutions and organizations are such rights enshrined in the Constitution as the right to judicial protection and qualified legal assistance, the right of a citizen to get acquainted with the content of information concerning his rights and legitimate interests. The purpose of the article is to ensure the authority of a lawyer to request information of procedural importance, to give scientifically grounded proposals for improving the rules governing the right of a lawyer to request and demand information. The object of the research is the activities of a defense lawyer in sending requests to state bodies and organizations for obtaining information and the activities of these bodies and organizations in issuing it. The subject of the research is the theoretical basis and legal norms governing the activities of a defense lawyer in sending requests to state bodies and organizations for obtaining information and the activities of these bodies and organizations for its issuance. The study determined the use of general scientific methods, systematic, formal-logical research approaches, and analysis of statistical data. The novelty of the article is due to the fact that consideration of the issues of ensuring access of the defender to procedural information refers to the strategic direction of the development of Kazakhstani legislation, proposals for its improvement are given.